Going global (again): gratitude and service learning in post-pandemic times. Issue 2 (17th February 2023) - McIntosh, Megan; Lakey, Elizabeth
ABSTRACT: This analysis employs the concept of gratitude to trace key 'moments' in students' global service learning placements. We problematise the uncritical promotion of interculturality as an outcome of such placements. We analyse common narratives of gratitude that emerge from students before, during and after international placements in the Global South. Through focusing on the lifecycle of service learning placement we examine how expressions and recipients of gratitude shift over time, often belying a truly reciprocal exchange assumed to be inherent in service learning. We employ Critical Discourse Analysis to unearth power inequities that emerge from the broader societal relations in which these placements occur. We conclude by looking back to inform how we move forward in a post COVID-19 era in which further punctuation of global inequities will require intensified care to build meaningful and reciprocal service learning activities abroad and at home.